1998
DOI: 10.1007/bf03042762
|View full text |Cite
|
Sign up to set email alerts
|

Die systematische Stellung der Euomphalidae (Gastropoda)

Abstract: The core group of Euomphalidae with the genera Euomphalus, Straparollus, Serpulospira, Phymatifer, Schizostoma, Nodeuomphalus n. g. (Devonian to Permian) are characterized by a cyrtoconic, openly coiled, planispiral protoconch. This character distinguishes them from members of the four extant subclasses of the Gastropoda (Archaeogastropoda, Neritimorpha, Caenogastropoda and Heterostropha) and places the Euomphaloidea at a similarly high taxonomic level, the new subclass Euomphalomorpha. With Euomphalopsis the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…The protoconch of modern archaeogastropods was discussed by Bandel (1982) and Haszprunar (1993); the latter referred to it as the trochoid condition. Generally, the concept of the classical archaeogastropods is currently more that of a grade rather than a clade (Hickman 1988;Haszprunar 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protoconch of modern archaeogastropods was discussed by Bandel (1982) and Haszprunar (1993); the latter referred to it as the trochoid condition. Generally, the concept of the classical archaeogastropods is currently more that of a grade rather than a clade (Hickman 1988;Haszprunar 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the concept of the classical archaeogastropods is currently more that of a grade rather than a clade (Hickman 1988;Haszprunar 1993). Bandel (1982) showed that modern archaeogastropods, unlike all other Recent gastropods, have an unmineralized, bilaterally symmetrical shell, which is mechanically deformed and then mineralized. This commonly results in a characteristic irregular spiral shape and the presence of pouches, which are typical for many archaeogastropod protoconchs.…”
Section: Discussionmentioning
confidence: 99%
“…-Szabó (2009) discussed the systematic placement of discohelicids in detail and placed this group in Euomphalina and Euomphalina in Vetigastropoda (see also Bandel & Frýda 1998, Nützel 2002a). The present representative Discohelix guembeli adds no new information about the debated relationships of Palaeozoic euomphalids and Mesozoic discohelicids.…”
Section: B C Amentioning
confidence: 99%
“…Thus all living vetigastropods lacking nacre originated after the Paleozoic time. The phylogenetic position of the extinct Euomphaloidea is uncertain (Bandel & Frýda 1998;Nützel 2002;Frýda et al , 2008a. There is no reason to place them, together with all other extinct Paleozoic archaeogastropod families, within the Vetigastropoda because the latter clade is diagnosed by anatomic features that cannot be examined in extinct groups.…”
Section: Discussionmentioning
confidence: 99%
“…Paleozoic Euomphaloidea as well as Macluritoidea may represent basal or sister taxa to the Archaeogastropoda (also including Vetigastropoda) as shown by their protoconch morphology (Frýda & Rohr 2006). The members of the first group lack nacre (Bandel & Frýda 1998), but there are no shell microstructure data for macluritoidean gastropods.…”
Section: Discussionmentioning
confidence: 99%